Analisis Prioritas Pemberian Cuti Karyawan Menggunakan Metode Pembobotan Entropy dan Simple Multi Attribute Rating Technique - Sitna Hajar Hadad (PT. Tech Cart Press, 2024)
Employee leave is a right given to employees to take free time or vacation without reducing salary or wages. This leave is important to maintain the health and well-being of employees, as well as to ensure that employees can feel valued and given the opportunity to live free time or vacation. Prioritizing employee leave is often a challenge, especially when there are many leave applications submitted simultaneously. The purpose of this study is to develop a system or model that can assist managers or human resources departments in making more informed and structured decisions regarding the provision of leave to employees. Using entropy and SMART weighting methods, this study helps to assess and give weight to the criteria that influence the priority of granting leave. The ranking results showed results, namely rank 1 in the provision of employee leave with a value of 0.8449 obtained by Employee 6, rank 2 in the provision of employee leave with a value of 0.8061 obtained by Employee 1, rank 3 in the provision of employee leave with a value of 0.5442 obtained by Employee 2, rank 4 in the provision of employee leave with a value of 0.465 obtained by Employee 3 and Employee 5, and 4th place in the provision of employee leave with a value of 0.0581 obtained by Employee 4. The results of this ranking become a recommendation for companies in setting leave priorities for existing employees, thus assisting company stakeholders in making decisions based on the results of recommendations carefully.